"We Brought It Upon Ourselves": University-Based Teacher Education and the Emergence of Boot-Camp-Style Routes to Teacher Certification - Daniel Friedrich (Arizona State University, 2014)
The proliferation of boot-camp-style routes to teacher certification in the last two decades is seen by many university-based teacher educators as the result of the advancement of conservative interests aimed at de-professionalizing teaching. This essay argues that this view only accounts for one piece of the answer, the other one being that some of the foundational assumptions embedded in most university-based teacher education programs actually opened the doors for the boiling down of teacher preparation to the bare minimum. By situating the psychological sciences at the foundations of pedagogical knowledge and positioning them as the privileged lens to understand the learning subject, university-based teacher education has paved the way to its own disappearance. Both traditional and alternative routes to teaching can be understood, then, as part of the same system of thought, one that needs to be cracked open in order to be able to imagine other possibilities.